The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1111/j.1755-5949.2009.00110.x
|View full text |Cite
|
Sign up to set email alerts
|

RESEARCH: Cognitive Rehabilitation for Bipolar Disorder: An Open Trial for Employed Patients with Residual Depressive Symptoms

Abstract: Introduction-Bipolar Disorder is characterized by recurrent episodes of depression and/or mania along with interepisodic mood symptoms that interfere with psychosocial functioning. Despite periods of symptomatic recovery, individuals with bipolar disorder often continue to experience impairments in psychosocial functioning, particularly occupational functioning. Two determinants of psychosocial functioning of euthymic (neither fully depressed nor manic) individuals with bipolar disorder are residual depressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
147
3
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(165 citation statements)
references
References 46 publications
8
147
3
7
Order By: Relevance
“…Furthermore, the identification of cross-disorder neuropsychological profiles could lend additional support to the cognitive continuum hypothesis (Ancín et al, 2010;Bora, Yucel, & Pantelis, 2009), which suggests that the differences in cognitive impairment between disorders such as schizophrenia and BD are quantitative rather than qualitative. These hypotheses have important implications for diagnostic classification as well as treatment planning, especially in light of the growing interest in cognitive and functional rehabilitation programs (Deckersbach et al, 2010;Torrent et al, 2011), which currently target each disorder as a whole, but could benefit from adjustments for the cognitive subprofiles displayed by each diagnostic category.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the identification of cross-disorder neuropsychological profiles could lend additional support to the cognitive continuum hypothesis (Ancín et al, 2010;Bora, Yucel, & Pantelis, 2009), which suggests that the differences in cognitive impairment between disorders such as schizophrenia and BD are quantitative rather than qualitative. These hypotheses have important implications for diagnostic classification as well as treatment planning, especially in light of the growing interest in cognitive and functional rehabilitation programs (Deckersbach et al, 2010;Torrent et al, 2011), which currently target each disorder as a whole, but could benefit from adjustments for the cognitive subprofiles displayed by each diagnostic category.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, three studies provided figures for withdrawals and dropouts. Deckersbach et al 17 reported five dropouts from 18 participants and Preiss et al 18 reported 21 dropouts out of 45 participants at study outset. Torrent et al 20 reported that 28.6% patients discontinued in the functional remediation group, 24.4% discontinued rehabilitation in BD are more likely to be published.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, our results also show that each CR program had its own specific aims, such as emotional and social training 19 or improvement of attention, memory and planning. 17 Similarly, while most of the CR programs comprised a total of approximately 17 hours, they varied in terms of the number of session per week, from one 20 to three. 18 emotional recognition and emotional perception.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations